2019
DOI: 10.1016/j.phrs.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hypertensive mechanisms of cyclic depsipeptide inhibitor ligands for Gq/11 class G proteins

Abstract: Augmented vasoconstriction is a hallmark of hypertension and is mediated partly by hyperstimulation of G protein couple receptors (GPCRs) and downstream signaling components. Although GPCR blockade is a key component of current anti-hypertensive strategies, whether hypertension is better managed by directly targeting G proteins has not been thoroughly investigated. Here, we tested whether inhibiting G q/11 proteins in vivo and ex vivo using natural cyclic depsipeptide, FR900359 (FR) from the ornamental plant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…Because inhibition of Gq/11 activity by more than 50% is likely to be lethal, as indicated by gene dosage studies in knockout mice ( 29 ), we sought to define protocols and conditions under which chronic, systemic administration of FR is physiologically tolerated, so we could assess the therapeutic potential of FR in mouse xenograft models of UM. Based on prior studies examining the acute effects of FR or the closely related inhibitor YM-254890 (YM) ( 22 , 24 , 39 ), we administered FR by subcutaneous injection at 0.1–3.0 mg/kg on alternate days for 30 days to define an LD 50 of ∼0.6 mg/kg in NOD-scid-gamma (NSG) mice used as xenograft recipients ( Fig. 5 A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because inhibition of Gq/11 activity by more than 50% is likely to be lethal, as indicated by gene dosage studies in knockout mice ( 29 ), we sought to define protocols and conditions under which chronic, systemic administration of FR is physiologically tolerated, so we could assess the therapeutic potential of FR in mouse xenograft models of UM. Based on prior studies examining the acute effects of FR or the closely related inhibitor YM-254890 (YM) ( 22 , 24 , 39 ), we administered FR by subcutaneous injection at 0.1–3.0 mg/kg on alternate days for 30 days to define an LD 50 of ∼0.6 mg/kg in NOD-scid-gamma (NSG) mice used as xenograft recipients ( Fig. 5 A ).…”
Section: Resultsmentioning
confidence: 99%
“…Critical issues and questions remain to be addressed, however. YM/FR may exert deleterious as well as therapeutically beneficial effects, because they do not discriminate between wild-type and oncogenic Gq/11 ( 14 ), and target Gq/11-dependent physiological systems ( 21 , 22 , 23 , 24 ) essential for homeostasis and viability ( 25 , 26 , 27 , 28 ). Indeed, YM/FR administered systemically at levels that reduce Gq/11 activity in host systems greater than 50% is likely to be lethal, as suggested by gene dosage studies of Gq/11 knockout mice ( 29 ).…”
mentioning
confidence: 99%
“…Blood pressure and heart rate responses to chronic administration of vehicle or FR900359 were monitored by radiotelemetry in conscious mice by following previously described procedures (24,51). Briefly, adult NSG male mice were implanted with a radiotelemetry pressuresensing catheter in the right carotid artery under isoflurane (3% mixed with 95% oxygen) anesthesia.…”
Section: Mouse Radiotelemetrymentioning
confidence: 99%
“…Critical issues and questions remain to be addressed, however. YM/FR may exert deleterious as well as therapeutically beneficial effects, because they do not discriminate between wild-type and oncogenic Gq/11 (14), and target Gq/11-dependent physiological systems (21)(22)(23)(24) essential for homeostasis and viability (25)(26)(27)(28). Indeed, YM/FR administered systemically at levels that reduce Gq/11 activity in host systems greater than 50% is likely to be lethal, as suggested by gene dosage studies of Gq/11 knockout mice (29).…”
Section: Introductionmentioning
confidence: 99%
“…Binding of YM and FR to the Gα q protein subunit is believed to prevent nucleotide exchange of GDP for GTP which keeps the heterotrimeric G protein arrested in its inactive state (Nishimura et al, 2010 ; Schrage et al, 2015 ). Inhibition of G q signaling has been investigated in several disease models, and FR in particular, due to its long residence time (Kuschak et al, 2020 ), was found to be a promising drug candidate for the treatment of complex diseases such as asthma (Matthey et al, 2017 ), hypertension (Meleka et al, 2019 ), metabolic syndrome (Klepac et al, 2016 ), and cancers (Onken et al, 2018 ; Annala et al, 2019 ; Lapadula et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%